Perbedaan Kadar Hemoglobin Anak Sekolah Sebelum dan Sesudah Pemberian Makanan Tambahan Anak Sekolah (PMT-AS) di SD Negeri Banyuanyar III Kota Surakarta Tahun 2012 - Geru, Iin Reni Astuti, Ir. Listyani Hidayati, M.Kes, Dyah Widowati, SKM (2013)
Background : Anemia is still world problem. Anemia prevalence for students in the world is 40%. In Indonesia, anemia prevalence for students is still high, 50%. In 2009, 54.7 % of students target for PMT-AS on Surakarta was anemia. In SD Negeri Banyuanyar III Surakarta, one of the target of PMT-AS in 2012 on Surakarta, 18.29% of students who were anemia, with the highest percentage was in class IV, 34.88%. To overcome the problem of malnutrition for students in SD/MI, a feeding food program (PMT -AS) was held. The program has an objective to increase physical endurance of students through nutrition rehabilitation and health so that it can increase the students learning interest and learning skill. Objective: To analize the difference of hemoglobin level in elementary schoolchildren before and after feeding food program (PMT-AS) on SD Negeri Banyuanyar III Surakarta in 2012. Research Method: This research is included in pre -experiment design with one group pretest-postest. Subjects of this research are 80 students from class III, IV, V in SD Negeri Banyuanyar III Surakarta that are taken by using Stratified Random Sampling. Hemoglobin level before and after feeding food program (PMT-AS) is measured by using cyanmethemoglobin by UPT of Puskesmas Banyuanyar Surakarta. Statistic analysis uses Paired Samples t Test. Result: Anemia status of the subjects decreased from 31.3% to 27.5% after feeding food program (PMT-AS). The average of hemoglobin level before feeding food program (PMT-AS) was 12.72 g/dL +1.33. The average of hemoglobin level after feeding food program (PMT-AS) was 12.80 g/dL + 1.50. Statistical analysis shows that there is no significant difference in hemoglobin level before and after feeding food program (PMT-AS) on SD Negeri Banyuanyar III Surakarta in 2012 (p=0.650). Conclusion : There is no significant difference of hemoglobin level of elementary schoolchildren before and after feeding food program (PMT -AS) on SD Negeri Banyuanyar III Surakarta in 2012.